Sexual orientation identity in relation to smoking history and alcohol use at age 18/19: cross-sectional associations from the Longitudinal Study of Young People in England (LSYPE) - Hagger-Johnson, Gareth (BMJ Publishing Group, 2013)
OBJECTIVES: Information about the health behaviours of minority groups is essential for addressing health inequalities. We evaluated the association among lesbian, gay or bisexual (LGB) sexual orientation identity and smoking and alcohol use in young people in England. DESIGN: Data drawn from wave 6 of the Longitudinal Study of Young People in England (LSYPE). SETTING: Self-completion questionnaires during home visits, face-to-face interviews and web-based questionnaires. PARTICIPANTS: Data from 7698 participants (3762 men) with information on sexual orientation identity and health behaviours at age 18/19. OUTCOME MEASURES: Cigarette smoking history, alcohol drinking frequency and risky single occasion drinking (RSOD). RESULTS: LGB identity was reported by 3.1% of participants (55 gay, 33 lesbian, 35 bisexual male, 111 bisexual female), 3.5% when adjusting for the survey design. Adjusting for a range of covariates, identification as lesbian/gay was found to be associated with smoking (OR=2.23, 95% CI 1.42 to 3.51), alcohol drinking >2 days/week (OR=1.99, 95% CI 1.25 to 3.17) and RSOD (OR=1.80, 95% CI 1.13 to 2.86) more than weekly. Bisexual identity was associated with smoking history (OR=1.84, 95% CI 1.30 to 2.61) but not alcohol drinking >2 days/week (OR=1.20, 95% CI 0.79 to 1.81) or RSOD (OR=1.04, 95% CI 0.71 to 2.86). CONCLUSIONS: In a sample of more than 7600 young people aged 18/19 years in England, lesbian/gay identity is associated with cigarette smoking, drinking alcohol frequency and RSOD. Bisexual identity is associated with smoking but not RSOD or frequent alcohol drinking.